The Effects of Cooperative Learning Model Three Minutes Review Towards Student’s Writing Skill (an Experiment at State Junior High School in Bekasi) - Reknosari Reknosari (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2017)
This research is aimed to get empirical data and analyze the effects of cooperative learning model three minutes review towards student’s writing skill at state junior high school in Bekasi. Data collection was done by giving test for writing test given to the eighth grade students at SMPN 24 Bekasi. Due to the result, it can be inferred that the result of writing skill of students is better to those who use cooperative learning model three minutes review. In relation to the result of the research, teachers are expected to use cooperative learning model three minutes review in motivating student’s writing skill. Teachers have to follow seminar and short courses in improving their teaching skills. School has to facilitate teachers and students in order to create conductive atmosphere of teaching and learning process. Key words: writing skill, cooperative learning model, three minutes review model